Dipeptidyl peptidase-4 inhibitor enhances restoration of salivary glands impaired by obese-insulin resistance - Jitjiroj Ittichaicharoen (2018)
© 2017 Elsevier Ltd Objective Chronic high-fat diet consumption causes not only obese- insulin resistance, but also leads to pathological changes in salivary glands, including increased mitochondrial dysfunction, apoptosis, oxidative stress, and inflammation. Dipeptidyl peptidase-4 inhibitor (vildagliptin) is an oral anti-diabetic drug, using for treatment of type 2 diabetes. Vildagliptin has been shown to exert beneficial effects on several organs in cases of obese-insulin resistant condition. However, the effect of vildagliptin on salivary glands impaired by obese-insulin resistance has not been investigated. The hypothesis in this study is that vildagliptin confers beneficial effects on the salivary gland impaired by obese-insulin resistance via decreasing mitochondrial dysfunction, apoptosis, oxidative stress, and inflammation. Design Twenty-four male Wistar rats were divided into two groups. Each group was fed with either a normal (ND; n = 8) or a high fat diet (HFD; n = 16) for 16 weeks. At week 13, the HFD-fed rats were subdivided into 2 subgroups to receive either a vehicle or vildagliptin (3 mg/kg/day) for 28 days via gavage feeding. ND-fed rats were treated with the vehicle. At the end of treatment, metabolic parameters were examined, and rats were killed. Submandibular glands were removed to appraise inflammatory markers, apoptosis and mitochondrial function. Results Vehicle-treated HFD-fed rats developed obese-insulin resistance with an increase in oxidative stress, inflammation, apoptosis, and mitochondrial dysfunction in the salivary glands. Vildagliptin therapy reduced oxidative stress, inflammation, apoptosis and mitochondrial dysfunction in salivary gland of HFD-fed rats. Conclusion Vildagliptin prevented salivary gland injury occurring due to obese-insulin resistance.